2010
DOI: 10.1016/j.bmcl.2010.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR studies of 1,4-benzoxazine MenB inhibitors: Novel antibacterial agents against Mycobacterium tuberculosis

Abstract: Menaquinone is an essential component of the electron transport chain in many pathogens and consequently enzymes in the menaquinone biosynthesis pathway are potential drug targets for the development of novel antibacterial agents. In order to identify leads that target MenB, the 1,4-dihydroxy-2-naphthoyl-CoA synthase from Mycobacterium tuberculosis, a high throughput screen was performed. Several 1,4-benzoxazines were identified in this screen and subsequent SAR studies resulted in the discovery of compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 19 publications
2
64
0
Order By: Relevance
“…Initial investigations into potential inhibitors of this enzyme were conducted by Li et al 34 where a coupled assay was used to screen over 105 000 drug-like molecules with a large structural diversity. From this bank of molecules, 455 molecules showed at least 30% enzyme inhibition relative to control, of which four compounds with a benzoxazine scaffold were chosen for further investigation.…”
Section: 33mentioning
confidence: 99%
“…Initial investigations into potential inhibitors of this enzyme were conducted by Li et al 34 where a coupled assay was used to screen over 105 000 drug-like molecules with a large structural diversity. From this bank of molecules, 455 molecules showed at least 30% enzyme inhibition relative to control, of which four compounds with a benzoxazine scaffold were chosen for further investigation.…”
Section: 33mentioning
confidence: 99%
“…Coumarin derivatives show various biological and pharmacological activities 37,38 . In addition to numerous activities of coumarin derivatives, they were reported to inhibit carbonic anhydrase activity 31,32 42 , antihypertensive 43 , anti-inflammatory 44 and other biological activities of 1,4-oxazinones and benzoxazines were reported [45][46][47][48] . Beside various biological activities of 1,4-oxazinone and benzoxazine derivatives, anticonvulsant activities of benzoxazinones were reported in the literature 48 .…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, Li et al [1] identified several 1,4-benzoxazine-2-one derivatives, that target MenB (1,4-dihydroxy-2-naphtoyl-CoA synthase), endowed with high antibacterial activity against Mycobacterium tuberculosis H37Rv with MIC values of 0.6 μg/mL (4 μg/mL our data). By these assumptions, we designed and synthesized some analogous compounds in order to investigate the SAR and to discover new potent antimycobacterial derivatives.…”
mentioning
confidence: 61%